(untitled) (Itinera, 2023)
This article aims to weave the fields of performativity, sound and urban living through philosophical itineraries that follow two motifs: mourning and vulnerability. Through Bonnie Honig’s rereading of Antigone, we will trace the characters of a performative Antigone, who hybridises the fields of phoné and logos in her lament. We will then consider the example of contemporary mourning as well as the problem of urban soundscape spread by an ubiquitous technophony. We will address the motif of vulnerability starting from the work and research of Brandon Labelle, who will accompany us on sound walks where listening will emerge as a performative practice. Listening to urban space confronts us with a global and generalised vulnerability. By combining mourning and vulnerability, we will finally express the need for a performativity of fragility in our global condition.